Distinguishing Zinc from Zinc Using Model Samples from 64Zn‐Depleted Zinc Oxide: Proof of Concept. Issue 23 (23rd September 2022) - Hassel, Achim Walter; Hafner, Martina
Abstract : As a proof of concept, distinction of different zinc layers on top of each other is presented here. It can be used for studying chemical reactions or corrosion processes. The use of the nonradioactive and relatively cheap 64 Zn‐depleted zinc oxide (DZO) is suggested, which yields a distinctly different isotope pattern with factor 72‐reduced 64 Zn content. From electrochemical depth profiling and a detection by mass spectrometry, that is, inductively coupled plasma mass spectrometry, thickness information can be derived. The reasonable price allows preparations on the lab scale and provides an elegant experimental approach for mechanistic studies. DZO is used as a source to deposit zinc films from alkaline or acidic solutions onto pure Fe or pure Zn. A flow‐type scanning droplet cell microscope is used for electrochemical depths profiling. It can be demonstrated that depth profiling is possible not only for dissimilar element combinations such as Zn on Fe but also Zn on Zn when detection of the deviating isotopic pattern is used tracing the rising 64 Zn signal. This method can also be used to prepare zinc films which are hardly radioactivated by neutrons. Further applications are in the determination of reaction mechanisms involving Zn or in the determination of Zn exchange current densities in electrochemistry. Abstract : Distinguishing Zn from Zn is proven here in an electrochemical dissolution transient of a thin 64 Zn‐depleted zinc layer. While all other Zn isotopes show an immediate increase after 114 s (violet line), the 64 Zn signal increases only after drilling through the Zn film into the zinc substrate with natural isotope pattern, that is, high 64 Zn content (red line).